SOCIO-POLITICAL MEANINGS OF THE PARTIES TO THE SPAIN-CATALAN CONFLICT THROUGH THE PRISM OF TWITTER COMMUNICATIONS - N. Yu. Matveeva; E. V. Olshanskaya (Сравнительная политика, 2020)
The purpose of this study is to analyze the social meanings of the network communicative activity of the parties of the Spanish-Catalan confl ict in a specific direction – in discussions about tweets of leading EU politicians. The relevance of the presented study is determined, on the one hand, by the increased infl uence of social media on political life, and, on the other hand, by the need to understand political confl icts not only as confl icts of interest, but also as confl icts of social meanings and ideas. The article discusses and interprets the meanings of two social communities ̃ supporters of the independence of Catalonia and supporters of the unity of Spain, implied in the communication carried out using the social network Twitter. The analysis is based on an empirical study of twitter messages by the method of quantitative and qualitative content analysis. The main socio-political attitudes of the parties to the confl ict, expressed in remarks on tweets of representatives of the EU leadership, are examined. The time interval of the study covers two years ̃ from May 2017 to June 2019. Based on an analysis of the level of communication activity of network users, it was revealed that the supporters of the independence of Catalonia act as a more active and cohesive social community, compared with the supporters of the unity of Spain. They have clear ideas about the political situation in the country and the region, as well as expressed ideological principles. This allows us to conclude that there is a narrative of independent Catalonia formed in public opinion. However, the meanings concerning the problems of social relations in the country and the region, arising in the light of the requirements of independence, remain in the shadow of communication. The passive nature of the participation of supporters of the unity of Spain in network communication in this area, as well as the content of their remarks, indicates the absence of a formed social base of supporters of unity, both among the inhabitants of Catalonia and among the rest of the Spanish citizens. This may be due to ideological lag, in which supporters of the country's unity are guided by outdated ideological stereotypes that are not able to unite them into a real social community with a certain political worldview. According to the findings of the study, it is precisely the ideas of the parties to the confl ict about social relations in the country that are their weak link that does not allow reaching a new level of political compromise or consensus.